Nucleic Acid Sensing Pathways in DNA Repair Targeted Cancer Therapy - Xie, Bingteng; Luo, Aiqin (Frontiers in Cell and Developmental Biology, 2022)
The repair of DNA damage is a complex process, which helps to maintain genome fidelity, and the ability of cancer cells to repair therapeutically DNA damage induced by clinical treatments will affect the therapeutic efficacy. In the past decade, great success has been achieved by targeting the DNA repair network in tumors. Recent studies suggest that DNA damage impacts cellular innate and adaptive immune responses through nucleic acid-sensing pathways, which play essential roles in the efficacy of DNA repair targeted therapy. In this review, we summarize the current understanding of the molecular mechanism of innate immune response triggered by DNA damage through nucleic acid-sensing pathways, including DNA sensing via the cyclic GMP-AMP synthase (cGAS), Toll-like receptor 9 (TLR9), absent in melanoma 2 (AIM2), DNA-dependent protein kinase (DNA-PK), and Mre11-Rad50-Nbs1 complex (MRN) complex, and RNA sensing via the TLR3/7/8 and retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs). Furthermore, we will focus on the recent developments in the impacts of nucleic acid-sensing pathways on the DNA damage response (DDR). Elucidating the DDR-immune response interplay will be critical to harness immunomodulatory effects to improve the efficacy of antitumor immunity therapeutic strategies and build future therapeutic approaches.